Communicating with stakeholders when bad news is uncertain. Issue 2 (8th May 2017) - Baker, Scott; Hernandez, Morela
Abstract : Purpose: The purpose of this paper is to explore the question of if and when leaders should communicate bad news to their stakeholders. Previous research in the crisis communication literature has highlighted the need to communicate quickly and persuasively to minimize losses; however, the authors argue that such tactics assume certainty in negative outcomes and tend to generate predominantly one-way, company-centric communication. In this paper, the authors propose that under conditions of uncertainty (i.e. when the bad news has an unknown outcome or cause) different communication strategies are needed. Design/methodology/approach: Drawing on the stakeholder theory, the authors argue that organizational decision makers have a clear moral obligation to share bad news with affected stakeholders. The authors then review the existing approach to crisis communication and discuss its limitations under conditions of uncertainty. Finally, the authors develop a set of scenarios to guide the communication of bad news under conditions of uncertainty. Findings: The authors formulate a framework to guide leaders on how to communicate with stakeholders when the nature of the bad news is uncertain and open to multiple interpretations. The authors propose a situational approach for responding to stakeholders that emerges from the context of the bad news. Originality/value: The authors propose a situational framework for communicating bad news that overcomes the current limitations of extant crisis communication strategies under conditions of uncertainty. This involves balancing existing crisis communication recommendations with a more collaborative sensemaking approach.